Evaluation of the RSR 3 screen ICA™ and 2 screen ICA™ as screening assays for type 1 diabetes in Sweden - Törn, Carina; Vaziri-Sani, Fariba; Ramelius, Anita; Elding Larsson, Helena; Ivarsson, Sten Anders; Amoroso, Marie; Furmaniak, Jadwiga; Powell, Michael; Smith, Bernard Rees (Acta diabetologica, 2022)
Aim The study aim was to evaluate the RSR 3 Screen ICA™ and 2 Screen ICA™ for detection of islet cell autoimmunity in healthy Swedish subjects and patients with newly diagnosed type 1 diabetes (T1D). Methods 3 Screen is designed for combined detection of autoantibodies to glutamic acid decarboxylase (GADA), to the islet antigen IA-2 (IA-2A) and to zinc transporter 8 (ZnT8A), while 2 Screen detects GADA and IA-2A. Serum samples from 100 T1D patients at onset and 200 healthy controls were studied. Results 3 Screen achieved 93% assay sensitivity and 97.5% specificity, while 2 Screen achieved 91% assay sensitivity and 98.5% specificity. Samples were also tested in assays for individual autoantibodies. There was only one 3 Screen positive healthy control sample (0.5%) that was positive for multiple autoantibodies (IA-2A and ZnT8A). In contrast, most of the 93 3 Screen positive patients were positive for multiple autoantibodies with 72% (67/93) positive for both GADA and IA-2A and 57% (53/93) positive for three autoantibodies (GADA, IA-2A and ZnT8A). Insulin autoantibodies (IAA, measured by radioimmunoassay) were positive in 13 patients and two healthy controls. Conclusion 3 Screen achieved high sensitivity and specificity, suitable for islet cell autoimmunity screening in a healthy population. In the case of 3 Screen positivity, further assays for GADA, IA-2A and ZnT8A are required to check for multiple autoantibody positivity, a hallmark for progression to T1D. In addition, testing for IAA in children below two years of age is warranted.